The nature of fairness in contracts: An electronic contract perspective - Dona Budi Kharisma; Agus Yudha Hernoko; Prawitra Thalib; Digvijay Singh Rana (Jurnal Hukum Novelty, 2025)
Introduction to the Problem: The development of information technology has given rise to various types of electronic contracts in the form of adhesion contracts. Unfair legal issues surround the contract formation process and the content of new electronic contract models, such as browser wrap agreements and sign-in wrap agreements. In several cases that have been decided by the Court, the panel of judges has its own standards for deciding disputes based on a fair electronic contract. Purpose/Study Objectives: This paper aims to elaborate on the nature of contractual fairness from an electronic contract perspective. Design/Methodology/Approach: This study employed the statute approach and the case approach. This research examines various regulations relating to agreements, electronic contracts, the doctrine of unconscionability and examizing a number of decisions pertaining to electronic contracts from courts in Indonesia as well as various other nations. Findings: The research results can be concluded that nature of fairness in electronic contracts can be tested through two indicators, the process of forming the contract and clauses in the agreement. Electronic contracts are considered procedurally unfair if the weak party does not know and realizes that they are bound by a contract. An electronic contract is considered substantively unfair if a clause in the contract places an unreasonable burden on the weaker party. In addition to the doctrine of unconscionability, the principles of transparency, duty to read, and reasonable expectation must also be used to ensure fairness in electronic contracts. These principles need to be formulated into the norms of the Indonesian Information Transaction Act to protect consumers from unfair contracts. Paper Type: Research Article